The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4103/ijem.ijem_441_17
|View full text |Cite
|
Sign up to set email alerts
|

Mutational profile of papillary thyroid carcinoma in an endemic goiter region of North India

Abstract: Introduction:Mitogen activated protein kinase (MAPK) pathway is regularly altered in papillary thyroid carcinomas (PTCs). Serine/threonine-protein kinase B-Raf (BRAF) V600E mutations were observed very frequently in PTC along with less frequent rat sarcoma (RAS) and rearranged during transfection (RET) gene, also known as RET/PTC translocation. The present study aimed to analyze the mutational profile of PTCs from an endemic Goiter area of North India.Methodology:Tissues from 109 PTC patients were used to isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We have also shown BRAF V600E mutation in 46% of PTC. Our finding has an intermediate position between Mediterranean countries and North American and some Far East countries [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 6). Some studies have close results to ours [28,29,30,35,36,38,39].…”
Section: Plos Onementioning
confidence: 99%
“…We have also shown BRAF V600E mutation in 46% of PTC. Our finding has an intermediate position between Mediterranean countries and North American and some Far East countries [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] (Table 6). Some studies have close results to ours [28,29,30,35,36,38,39].…”
Section: Plos Onementioning
confidence: 99%
“…This result seems to be similar to a study conducted in India, which reported RAS mutation in 20% of the patients. 33 Lower rate of RAS mutation was found in Saudi Arabia, in which the rate of RAS mutation was 6.1%. 34 Among the three homologous isoforms, NRAS was the most frequent mutation displayed in thyroid nodules.…”
Section: Discussionmentioning
confidence: 96%
“…Genetic studies looking into their role in ACS are scanty, especially in the Indian population [ 28 ]. In this context, we set out to study the prevalence and biological/clinical significance of these somatic mutations in our study population.…”
Section: Discussionmentioning
confidence: 99%